Effect of Dietary Education on Adolescent Women Aiming to Increase Calcareous Stiffness - Murakami, Toshio; Ikeda, Junko; Fukuda, Sayuri (Eiyōgaku zasshi, 2004)
This study was conducted to identify how best to educate adolescent women on nutrition to improve their dietary habits and how this improvement can lead to increased calcareous stiffness. The calcareous stiffness, dietary habits and living conditions of the subjects were first evaluated. Those whose calcareous stiffness was relatively low were randomly divided into two groups; an education group and control group. Those in the education group were given advice based on the evaluation of their dietary habits. A little less than 6 months after that, each subject in the education group started to keep a dietary record and details of the improvement steps taken, while continuing with appropriate education concerning dietary habits and health. The calcareous stiffness of each subject was then determined for the second time, and the usefulness of the nutritional education was discussed. The results of this study show that the subjects in the education group improved in their dietary habits when compared to those in the control group. A before and after difference in the calcareous stiffness was apparent in the subjects of the education group, but not in those of the control group, demonstrating that the increase in calcareous stiffness was related to the nutritional education. Although the relationship between the change in calcareous stiffness and that of dietary habits should be further investigated, the education method used in this study proved to be very effective for improving dietary habits.